THE EFFECTIVENESS OF TIKTOK APPLICATION ON STUDENTS’ SPEAKING SKILL MOTIVATION - Qodarsih, Inna Anzalina; Sudarsono, Sudarsono; Suhartono, Luwandi; Ikhsanudin, Ikhsanudin; Rahmani, Eka Fajar (Universitas Muhammadiyah Ponorogo, 2023)
This study has a problem that students have low motivation in speaking skill and the aim of this study is to examine how the size of the TikTok application affected on students’ speaking skill motivation of tenth-grade students at SMAN 1 Sungai Raya in the academic year 2021/2022. Pre-experimental one-group pre-test and post-test design is used in this research process. The researcher selected X Mia 3 by using the purposive sampling technique consisting of 32 students. The questionnaire sheet is the instrument used in this study. Pre-test and post-test data were collected and analyzed using a t-test. This study found that the average pre-test score was 79.43 and the post-test score was 84.53. The result of the t-test was 5.86. The t-table with 31 degrees of freedom (df) and a significance at level 0.05 was 2.03. Analysis of the data revealed that the null hypothesis (Ho) is rejected, and the alternative hypothesis (Ha) is accepted because the t-test was higher than the t-table (5.862.03). In addition, the effect size was 0.99, which is classified as a very strong effect (0.8). Thus, implementing the TikTok application very strong affects students' speaking skill motivation.